The case of the stolen sixpence - Webb, Holly (Webb, Holly. Mysteries of Maisie Hitchins, 2014)
Junior sleuth Maisie Hitchins, who lives in her grandmother's boarding house in Victorian London, uncovers an intriguing plot involving stolen sausages, pilfered halfpennies, and a fast-paced bicycle chase.